Correction: Enantioselective synthesis of isochromans and tetrahydroisoquinolines by C–H insertion of donor/donor carbenes. Issue 19 (6th May 2020) - Nickerson, Leslie A.; Bergstrom, Benjamin D.; Gao, Mingchun; Shiue, Yuan-Shin; Laconsay, Croix J.; Culberson, Matthew R.; Knauss, Walker A.; Fettinger, James C.; Tantillo, Dean J.; Shaw, Jared T.
Abstract : Correction for 'Enantioselective synthesis of isochromans and tetrahydroisoquinolines by C–H insertion of donor/donor carbenes' by Leslie A. Nickerson et al., Chem. Sci., 2020, 11, 494–498, DOI: ; 10.1039/C9SC05111B .